Revised Classification of Epilepsies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The proposals for a revised classification of epilepsy and epileptic syndromes (1981-1985) have again been revised by the Commission on Classification and Terminology of the International League Against Epilepsy.